Savanna fires and their impact on net ecosystem productivity in North Australia - JASON BERINGER; LINDSAY B. HUTLEY; NIGEL J. TAPPER; LUCAS A. CERNUSAK (Global Change Biology, 2007)
Savannas comprise a large area of the global land surface and are subject to frequent disturbance through fire. The role of fire as one of the primary natural carbon cycling mechanisms is a key issue in considering global change feedbacks. The savannas of Northern Australia burn regularly and we aimed to determine their annual net ecosystem productivity (NEP) and the impact of fire on productivity. We established a long‐term eddy covariance flux tower at Howard Springs, Australia and present here 5 years of data from 2001 to 2005. Fire has direct impacts through emissions but also has indirect effects through the loss of productivity due to reduced functional leaf area index and the carbon costs of rebuilding the canopy. The impact of fire on the canopy latent energy exchange was evident for 40 days while the canopy was rebuilt; however, the carbon balance took approximately 70 days to recover. The annual fire free NEP at Howard Springs was estimated at −4.3 t C ha −1 yr −1 with a range of −3.5 to −5.1 t C ha −1 yr −1 across years. We calculated the average annual indirect fire effect as +0.7 t C ha −1 yr −1 using a neural network model approach and estimated average emissions of fine and coarse fuels as +1.6 t C ha −1 yr ‐1 . This allowed us to calculate a net biome production of −2.0 t C ha −1 yr ‐1 . We then partitioned this remaining sink and suggest that most of this can be accounted for by woody increment (1.2 t C ha −1 yr ‐1 ) and shrub encroachment (0.5 t C ha −1 yr ‐1 ). Given the consistent sink at this site, even under an almost annual fire regime, there may be management options to increase carbon sequestration by reducing fire frequency.